Oligoarticular Tuberculous Infection of the Knee and Acromioclavicular Joints: An Unusual Manifestation and Characteristic Magnetic Resonance Imaging Findings - Remzi ÇEVİK and Yaşar BÜKTE and Kemal NAS and Figen CEYLAN ÇEVİK and Gökhan KIRBAŞ and Hüseyin BÜYÜKBAYRAM (Archives of Rheumatology, 2011)
An increased incidence of tuberculosis has been seen in recent years due to factors such as immunocompromising diseases and drug use. There has also been an increase in osteoarticular involvement. In this article, we report a 22-yearold male patient who was diagnosed with tuberculosis of the knee and acromioclavicular joints. Tuberculosis of this joint is very rare, and concomitancy with the knee has not been reported in the literature. The definitive diagnosis was performed by the histopathological examination of a synovial biopsy. The chest radiograph showed cavitation and the magnetic resonance imaging examination showed characteristic demonstrative findings. Antituberculosis drug treatment was started with a satisfactory response.